Successful implementation of outpatient R ± DHAX (rituximab, dexamethasone, oxaliplatin, cytarabine) for select patients with lymphoma: a single-center experience. Issue 4 (21st March 2022) - Pak, Terry K.; Dixon, Brianne N.; Buege, Michael J.; Dao, Phuong H.; Leary, Megan H.; Jarrett, Joy C.; Duggan, Tara A.; Caron, Philip; Falchi, Lorenzo; Hamlin, Paul; Hamilton, Audrey; Matasar, Matthew J.; et al.
Abstract: R ± DHAX has been traditionally administered to inpatient due to the timing of chemotherapy administration and the perceived need for close monitoring of adverse effects. To administer R ± DHAX outpatient, a multidisciplinary task force created clinical and educational guidelines which were implemented through two phases: pilot and expansion. The pilot program determined the feasibility of transitioning R ± DHAX outpatient at a single infusion site. The expansion phase led to a service-wide implementation across all outpatient sites. A total of 40 patients were included, of which 23 patients completed all cycles, outpatient, 12 transitioned inpatient to outpatient administration, and 5 transitioned outpatient to inpatient administration. The success rate of outpatient R ± DHAX administration was 90% (36 patients successfully completed outpatient administration/40 total patients). No cytarabine-related cerebellar or ophthalmic toxicity was reported. Outpatient R ± DHAX saved 192 hospital days. R ± DHAX could be successfully administered outpatient with minimal safety concerns and reduced hospital bed utilization.